2017
DOI: 10.1002/cbin.10718
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of nucleolus in the tobacco male meiocytes involved in cytomixis

Abstract: Behavior of nucleolus during the nuclear migration between plant cells (cytomixis) is studied for the first time in the tobacco male meiosis. As is shown, the nucleolus is located in a nonrandom manner in the migrating nuclei. In the majority of cases, the nucleolus resides on the nuclear pole strictly opposite to the cytomictic channel. Owing to this localization, the nucleolus extremely rare enters the recipient cell, so that the nucleolar material is in most cases undetectable in the micronuclei formed afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Cytomixis has been reported to occur along cytomictic channels [26,27,41,42], and cytomixis during the prophase of the first meiotic division is widespread in plant species and is evolutionarily important . CC-BY 4.0 International license perpetuity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytomixis has been reported to occur along cytomictic channels [26,27,41,42], and cytomixis during the prophase of the first meiotic division is widespread in plant species and is evolutionarily important . CC-BY 4.0 International license perpetuity.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that irregular cytomixis may be caused by various disturbances such as the structure of the cytomictic channels, synthesis of the callose coat, cell wall formation, the structure of the cell cytoskeleton and genetic unbalance [27,42]. As has been reviewed, the microtubular apparatus does not play an obvious role in the process of cytomixis in tobacco [26,42,47,48]. Furthermore, asymmetrical deposition of the callose wall occurred at similar ratio at the zygotene of meiosis I in the PMCs of both the F1-S fertile and F1-D sterile hybrids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The migrating chromatin displays no signs of inactivation or damage and, most likely, is represented by Analysis of cytoskeleton in the cells involved in cytomixis: the migrated chromatin displays an MT-organizing activity and can interact with the spindle Institute of Molecular Biology, Slovak Academy of Sciences 2019 whole chromosomes. Cells involved in cytomixis also show no signs of programmed cell death (Mursalimov et al , 2017. See the relevant reviews for more comprehensive information (Lone and Lone 2013;Mandal et al 2013;Mursalimov and Deineko 2018).…”
Section: Introductionmentioning
confidence: 99%